An exploratory human study of superstable homogeneous lipiodol–indocyanine green formulation for precise surgical navigation in liver cancer. Issue 2 (10th September 2022) - He, Pan; Xiong, Yongfu; Luo, Bin; Liu, Jianming; Zhang, Yang; Xiong, Yu; Su, Song; Fang, Cheng; Peng, Yisheng; Cheng, Hongwei; Chu, Chengchao; Mao, Jingsong; et al.
Abstract: The clinical applications of transcatheter arterial embolization (TAE) conversion therapy combined with hepatectomy have been severely restricted by ill‐defined tumoral boundaries and miniscule hidden lesions. Fluorescent surgical navigation is a promising method for overcoming these barriers. However, sufficient delivery of the fluorescent probe into the tumor region after long‐term TAE is challenging due to blockade of the tumor‐supplying artery. Here, a super‐stable homogeneous intermix formulating technology (SHIFT) to physically mix lipiodol and indocyanine green (ICG) formulation (SHIFT and ICG) for fluorescent surgical navigation after long‐term TAE conversion therapy is provided. Through the retrospective study of 45 clinical liver cancer patients, it is found that SHIFT and ICG formulation have excellent tumor deposition effect and safety. During surgical resection after long‐term TAE conversion therapy, SHIFT and ICG could clearly identify in real time the full tumor regions and boundaries and had a high signal‐to‐normal tissues ratio—even the indistinguishable satellite lesions could be identified with a strong fluorescence intensity. Meanwhile, SHIFT and ICG could improve operative, anesthetic, and postoperative variables associated with postoperative complications. This simple and effective SHIFT could provide precise fluorescent navigation for surgical resection following long‐term embolization therapy in clinical practice and has great potential for a translational pipeline.